PENGARUH E-FILLING, PENGETAHUAN PERPAJAKAN DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM SELATAN - Sianipar, Cutliyana; Wage, Sunarto (SCIENTIA JOURNAL, 2022)
The purpose of this study is to identify how much influence the implementation of E-filing, Tax Knowledge and Service Quality has on taxpayer compliance at KPP Pratama Batam Selatan. This data collection was carried out using a questionnaire which was measured using a Likert scale. The population taken in this study are individual taxpayers who have been registered at KPP Pratama Batam Selatan totaling 346,849 people and the sampling technique is carried out using the slovin formula calculation. personal. The data analysis method used in this study is quantitative data analysis with data collection techniques, namely descriptive analysis, validity test, reliability test, multiple linear regression test, normality test, multicollinearity test, heteroscedasticity test, F test, T test and determination test. . The data is processed using SPSS 25. The results show that E- filing affects taxpayer compliance, tax knowledge affects taxpayer compliance, service quality affects taxpayer compliance and together with e-filing, tax knowledge and service quality affects compliance. taxpayers at KPP Pratama South Batam. Keywords: Taxpayer Compliance; E-filing; Tax Knowledge; Service quality